Egocentric Content and the Complex Subject. - Skrzypulec, Błażej (Erkenntnis, 2025)
While it is commonly observed that visual experiences have an egocentric character, it is less clear how to properly characterize it. This manuscript presents a new argument in favor of a thesis that (a) visual experiences represent a subject-element, i.e., an element to which the perceived objects stand in egocentric relations, and (b) the subject-element is represented as a complex bodily structure. More specifically, it is argued that there are two plausible interpretations of directional perceptual qualities such as 'being to the left': (a) representing directional qualities consists in representing objects as having intrinsic properties, or (b) representing directional qualities consists in representing objects as related to parts of the bodily structure. Relying on this observation, it is shown that only the second option can explain the role of directional qualities in action selection based on visual experiences. Consequently, the most plausible interpretation of directional qualities is that, in representing objects as being to the left or right, visual experiences represent objects as being related to parts of the bodily structure.